Method for manufacturing copper iodide semiconductor material and mixed solution for manufacturing copper iodide semiconductor material

KR103021374B1Active Publication Date: 2026-09-16RES & BUSINESS FOUND SUNGKYUNKWAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020250043202
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2026-09-16
Estimated Expiration
2045-04-03

Smart Images

  • Figure 112025037444777-PAT00001_ABST
    Figure 112025037444777-PAT00001_ABST
Patent Text Reader

Abstract

The present invention discloses a method for manufacturing a copper iodide (CuI) semiconductor material and a mixed solution for manufacturing a copper iodide semiconductor material. The present invention comprises a thin film formation step of forming a thin film by spin-coating a mixed solution, in which copper iodide powder is dissolved in a mixed solvent, onto a substrate, and a heat treatment step of annealing the thin film, wherein the mixed solvent comprises two or more selected from acetonitrile (ACN), γ-butyrolactone, dimethylformamide (DMF), and dimethylsulfoxide (DMSO). According to the present invention, a high-quality copper iodide semiconductor material having high crystallinity can be provided compared to a technique using a single solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing a copper iodide semiconductor material and a method for manufacturing a copper iodide semiconductor material, and more specifically, to a method for manufacturing a copper iodide semiconductor material and a method for manufacturing a copper iodide semiconductor material capable of providing a high-quality copper iodide semiconductor thin film usable in the fields of electronics, energy, and display. Background Technology

[0002] Copper iodide (CuI), one of the metal halide semiconductors, has been studied as a next-generation transparent p-type semiconductor material due to its wide bandgap of 3.1 eV and high hole mobility. Due to the low copper (Cu) vacancy generation energy unique to CuI, it can be utilized not only as a semiconductor but also as a conductor.

[0003] According to published literature, research has been conducted to reduce the hole concentration of CuI by doping it with ZnI2 as a dopant via a solution process, thereby utilizing it as a channel layer for thin-film transistors. Additionally, studies have been reported on utilizing CuI as a transparent p-type electrode by doping it with sulfur (S) using various organic molecules, including sulfur (S), via a solution process. As such, these studies involve controlling electrical properties through extrinsic doping of the CuI matrix material; accordingly, the technology to enhance the hole mobility of the pure CuI thin film itself is considered a crucial factor in further increasing its applicability as a semiconductor or electrode.

[0004] However, according to previously published literature, it has been reported that when forming CuI thin films using a single solvent system with acetonitrile, problems such as roughness and broken connections occur. Prior art literature

[0005] Registered Patent Publication No. 10-1742073 (June 1, 2017) The problem to be solved

[0006] One objective of the present invention is to provide a method for manufacturing a copper iodide semiconductor material using a solution process utilizing a mixed solvent system.

[0007] Another objective of the present invention is to provide a mixed solution for manufacturing a copper iodide semiconductor material capable of manufacturing a high-quality copper iodide semiconductor material with high hole mobility. means of solving the problem

[0008] A method for manufacturing a copper iodide semiconductor material for one purpose of the present invention comprises a thin film formation step of forming a thin film by spin-coating a mixed solution in which copper iodide powder is dissolved in a mixed solvent onto a substrate, and a heat treatment step of annealing the thin film, wherein the mixed solvent comprises two or more selected from acetonitrile, γ-butyrolactone, dimethylformamide, and dimethylsulfoxide.

[0009] In one embodiment, the mixed solvent may include acetonitrile and dimethylsulfoxide.

[0010] In one embodiment, the volume ratio of the acetonitrile and dimethyl sulfoxide may be greater than 6:4 and less than or equal to 4:6.

[0011] In one embodiment, the mixed solvent may include acetonitrile and γ-butyrolactone.

[0012] In one embodiment, the volume ratio of the acetonitrile and γ-butyrolactone may be greater than 8:2 and less than or equal to 6:4.

[0013] In one embodiment, the mixed solvent may include acetonitrile and dimethylformamide.

[0014] In one embodiment, the volume ratio of the acetonitrile and dimethylformamide may be greater than 8:2 and less than or equal to 6:4.

[0015] In one embodiment, the thin film formation step can be performed in an inert atmosphere.

[0016] In one embodiment, the inert atmosphere can be formed using at least one of N2, Ar, and He.

[0017] In one embodiment, the heat treatment step can be performed at 70°C to 90°C.

[0018] A mixed solution for manufacturing a copper iodide semiconductor material for another purpose of the present invention is a mixed solution in which copper iodide powder is dissolved in a mixed solvent, wherein the mixed solvent comprises two or more selected from acetonitrile, γ-butyrolactone, dimethylformamide, and dimethylsulfoxide.

[0019] In one embodiment, the mixed solvent may include acetonitrile and dimethylsulfoxide.

[0020] In one embodiment, the volume ratio of the acetonitrile and dimethyl sulfoxide may be greater than 6:4 and less than or equal to 4:6. Effects of the invention

[0021] According to the present invention, a high-quality copper iodide semiconductor material having improved crystallinity and electrical properties without increasing or decreasing crystal defects, and high hole mobility can be provided.

[0022] Furthermore, according to the present invention, such copper iodide semiconductor material can provide excellent utility in fields such as next-generation CuI-based transparent p-type semiconductor materials and transparent p-type electrode materials, enabling innovative applications in next-generation displays and electronic products. Brief explanation of the drawing

[0023] FIG. 1 is a diagram for comparing and explaining the conventional method of manufacturing a copper iodide semiconductor material and the method of manufacturing a copper iodide semiconductor material of the present invention. FIG. 2 is a flowchart illustrating the method for manufacturing the copper iodide semiconductor material of the present invention. Figure 3 is the result of evaluating the solubility of a mixed solution (ACN:γ-butyrolactone) according to Example 1 of the present invention. Figure 4 is the result of evaluating the solubility of a mixed solution (ACN:DMF) according to Example 2 of the present invention. Figure 5 is the result of evaluating the solubility of a mixed solution (ACN:DMSO) according to Example 3 of the present invention. Figure 6 is the result of evaluating whether copper iodide powder precipitates in a mixed solution (ACN:DMSO) according to Example 3 of the present invention. Figure 7 is a diagram comparing the X-ray diffraction patterns of copper iodide thin films prepared using a single solvent (ACN) and a mixed solvent (ACN:DMSO=4:6) according to one embodiment of the present invention. FIG. 8 is a diagram comparing the X-ray diffraction patterns of a copper iodide thin film prepared using a mixed solvent according to one embodiment of the present invention before and after heat treatment, respectively. Figure 9 is a diagram comparing AFM surface morphology images of copper iodide thin films prepared using a single solvent (ACN) and a mixed solvent (ACN:DMSO=4:6) according to one embodiment of the present invention. FIG. 10 shows secondary electron microscope images of a copper iodide thin film prepared using a mixed solvent (ACN:DMSO = 4:6) according to one embodiment of the present invention, before and after heat treatment, respectively. FIG. 10a and FIG. 10b show surface morphology images of the copper iodide thin film using the mixed solvent immediately after spin coating at magnifications of 5,000x and 50,000x, respectively. FIG. 10c and FIG. 10d show surface morphology images of the copper iodide thin film using the mixed solvent after heat treatment at magnifications of 5,000x and 50,000x, respectively. FIG. 10e and FIG. 10f show surface morphology images at magnifications of 5,000x and 50,000x, respectively, confirmed by heat treating the sample of FIG. 10a immediately after measurement. FIG. 11 is an AFM surface morphology image of a copper iodide thin film prepared using a mixed solvent (ACN:DMSO = 4:6) according to one embodiment of the present invention when sufficiently exposed to air without heat treatment. FIG. 12 is an AFM surface morphology image of a copper iodide thin film prepared using a mixed solvent (ACN:DMSO = 4:6) according to one embodiment of the present invention after heat treatment. FIG. 13 is a figure showing the results of measuring the Hall effect of a copper iodide semiconductor thin film prepared using a mixed solvent (ACN:DMF and ACN:DMSO) mixed in various volume ratios according to one embodiment of the present invention. FIG. 14 is a figure showing the results of measuring the hole mobility of a copper iodide semiconductor thin film prepared using a mixed solvent (ACN:DMSO) mixed in various volume ratios (10:0, 8:2, 6:4, 4:6, 2:8, 0:10) according to one embodiment of the present invention. Specific details for implementing the invention

[0024] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the attached drawings. However, the technical concept of the present invention is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided to ensure that the disclosed content is thorough and complete and to ensure that the concept of the present invention is sufficiently conveyed to those skilled in the art.

[0025] In this specification, when a component is described as being on another component, it means that it may be formed directly on the other component or that a third component may be interposed between them. Additionally, in the drawings, the thicknesses of the films and regions are exaggerated for the effective description of the technical content.

[0026] Additionally, although terms such as first, second, third, etc., have been used to describe various components in the various embodiments of this specification, these components should not be limited by such terms. These terms are used merely to distinguish one component from another. Accordingly, what is referred to as the first component in one embodiment may be referred to as the second component in another embodiment. Each embodiment described and illustrated herein also includes its complementary embodiment. Furthermore, in this specification, "and / or" is used to mean including at least one of the components listed before and after it.

[0027] In the specification, singular expressions include plural expressions unless the context clearly indicates otherwise. Furthermore, terms such as "include" or "have" are intended to specify the existence of the features, numbers, steps, components, or combinations thereof described in the specification, and should not be understood as excluding the existence or addition of one or more other features, numbers, steps, components, or combinations thereof. Additionally, in this specification, "connection" is used to include both indirectly connecting multiple components and directly connecting them.

[0028] Furthermore, in describing the present invention below, if it is determined that a detailed description of related known functions or configurations could unnecessarily obscure the essence of the invention, such detailed description will be omitted.

[0030] Figure 1 is a diagram for comparing and explaining a conventional method for manufacturing copper iodide semiconductor materials and a method for manufacturing copper iodide semiconductor materials.

[0031] Referring to FIG. 1, the conventional method for manufacturing copper iodide semiconductor materials involves using a solution in which copper iodide powder is dissolved in a single solvent. However, copper iodide semiconductor materials manufactured using a single solvent have problems such as relatively large crystal grains growing, crystals being oriented in various directions on the substrate as they grow and not being completely aligned, and having somewhat irregular crystal grain boundaries. To solve these problems, the present invention provides a method for manufacturing copper iodide semiconductor materials using a mixed solvent instead of a single solvent. When a mixed solvent is used, compared to the conventional technology, the crystals are aligned in a certain direction, so a high-quality thin film can be obtained.

[0033] FIG. 2 is a flowchart illustrating the method for manufacturing the copper iodide semiconductor material of the present invention.

[0034] Referring to FIG. 2, the method for manufacturing a copper iodide semiconductor material of the present invention includes a thin film formation step (S10) of forming a thin film by spin-coating a mixed solution in which copper iodide (CuI) powder is dissolved in a mixed solvent onto a substrate, and a heat treatment step (S20) of annealing the thin film.

[0035] The above mixed solvent may include two or more selected from acetonitrile (ACN), γ-butyrolactone, dimethylformamide (DMF), and dimethylsulfoxide (DMSO). The above mixed solvent may include acetonitrile and any one of the substances selected from γ-butyrolactone, dimethylformamide, and dimethylsulfoxide. In the prior art, only acetonitrile was used as a single solvent. However, the present invention is characterized by using a mixture of other solvents with the acetonitrile solvent.

[0036] In one embodiment, the mixed solvent may include acetonitrile and dimethyl sulfoxide, and the volume ratio of the acetonitrile and dimethyl sulfoxide may be greater than 8:2 and less than or equal to 2:8. Preferably, the volume ratio of the acetonitrile and dimethyl sulfoxide may be greater than 6:4 and less than or equal to 4:6. In particular, when the volume ratio of the acetonitrile and dimethyl sulfoxide is 4:6, the copper iodide semiconductor material or thin film produced may have a hole mobility approximately three times higher than that of the prior art produced using a single solvent.

[0037] In another embodiment, the mixed solvent may include acetonitrile and γ-butyrolactone. The γ-butyrolactone may be added in an amount of 40% or less relative to the total mixed solvent. If this amount is exceeded, there may be a problem in that the copper iodide powder is not uniformly dissolved in the mixed solution. Therefore, preferably, the volume ratio of acetonitrile and γ-butyrolactone in the mixed solvent may be greater than 8:2 and less than or equal to 6:4.

[0038] In another embodiment, the mixed solvent may include acetonitrile and dimethylformamide. The dimethylformamide may be added in an amount of 40% or less relative to the total mixed solvent. If this amount is exceeded, there may be a problem in that the copper iodide powder is not uniformly dissolved in the mixed solution. Therefore, preferably, the volume ratio of acetonitrile and dimethylformamide in the mixed solvent may be greater than 8:2 and less than or equal to 6:4.

[0039] As such, the present invention is characterized by using a mixed solvent of various embodiments. Compared to when a copper iodide semiconductor material is manufactured using a single solvent as in the prior art, using the mixed solvent of the present invention can further improve the solubility of the copper iodide powder, the crystal growth of the copper iodide semiconductor material, and the uniformity of the thin film, thereby ultimately providing a high-quality copper iodide semiconductor material.

[0040] The above mixed solution may be prepared and / or stored in an inert atmosphere. The inert atmosphere may be established using at least one of N2, Ar, and He, but conditions such as the type and flow rate of the gas are not specifically limited; any material and condition capable of providing an inert atmosphere is acceptable. When stored in an inert atmosphere, the mixed solution can be stored in a uniformly mixed state without precipitates. Therefore, preferably, the mixed solution may be stored in an inert atmosphere after preparation.

[0041] In the above thin film formation step (S1), any substrate intended to form a copper iodide semiconductor material can be used, and the material is not specifically limited. For example, the substrate may be a glass substrate, an Al2O3 substrate, a semiconductor substrate, etc., and may also be a substrate having a multilayer structure in which a plurality of layers are stacked. For example, in a thin film transistor, a structure having a stacked structure of layers such as a substrate, an insulating layer, and an electrode layer may be used as a substrate to form a semiconductor layer.

[0042] The spin coating described above is a step performed to uniformly form the copper iodide semiconductor material on the substrate. In the present invention, spin coating conditions such as the execution time and rotation speed are not specifically limited, and the conditions of the spin coating can be easily changed to form a thin film of a desired thickness.

[0043] In one embodiment, the spin coating may be performed in an inert atmosphere. The inert atmosphere may be formed using at least one of N2, Ar, and He, but conditions such as the type and flow rate of the gas are not specifically limited; any material and condition capable of providing an inert atmosphere is acceptable. Thus, performing spin coating in an inert atmosphere can provide effects such as forming a uniform thin film, preventing oxidation of the mixed solution, and minimizing the influence of moisture on thin film formation.

[0044] The above heat treatment step (S20) may be performed to improve the crystallinity of the copper iodide semiconductor material or thin film, remove impurities, and enhance electrical properties. If heat treatment is not performed, there may be a problem in that the copper iodide semiconductor material formed on the substrate exists in a mixed form of disordered crystal nuclei, such as powder, and intermediate thin films. Therefore, in the present invention, it is preferable to perform the heat treatment step (S20) after the thin film formation step (S10).

[0045] In one embodiment, the heat treatment step (S20) can be performed at a low temperature. By performing the heat treatment step (S20) at a low temperature, the mixed solvent remaining in the thin film can be slowly evaporated to induce the formation of a uniform thin film, the thin film can be grown stably while protecting the substrate on which the thin film is formed, and the thin film can be induced to have a highly oriented structure. Preferably, the heat treatment step (S20) may be performed at 70°C to 90°C. More preferably, the heat treatment step (S20) may be performed at 80°C.

[0047] Referring again to FIG. 1, the copper iodide semiconductor material manufactured using the mixed solvent of the present invention forms a crystal structure aligned in a uniform direction, and in particular, has high orientation overall as it grows in the CuI (111) direction. That is, when manufacturing the copper iodide semiconductor material using the mixed solvent, high crystal orientation of the copper iodide semiconductor material and dominant growth of the CuI (111) plane can be induced. Therefore, the semiconductor material manufactured using the mixed solvent has high crystal orientation, so the charge transport path is optimized, and because the thin film is formed uniformly due to uniform crystal growth, it has the effect of having improved hole mobility.

[0049] The mixed solution for manufacturing a copper iodide semiconductor material according to the present invention is characterized in that, in a mixed solution in which copper iodide powder is dissolved in a mixed solvent, the mixed solvent comprises two or more selected from acetonitrile (ACN), γ-butyrolactone, dimethylformamide (DMF), and dimethylsulfoxide (DMSO).

[0050] The above mixed solvent may comprise acetonitrile and any one of a substance selected from γ-butyrolactone, dimethylformamide, and dimethylsulfoxide. In the prior art, only acetonitrile was used as a single solvent. However, the present invention is characterized by using a mixture of another solvent with the acetonitrile solvent.

[0051] In one embodiment, the mixed solvent may include acetonitrile and dimethyl sulfoxide, and the volume ratio of the acetonitrile and dimethyl sulfoxide may be greater than 8:2 and less than or equal to 2:8. Preferably, the volume ratio between the acetonitrile and dimethyl sulfoxide may be greater than 6:4 and less than or equal to 4:6. In particular, when the volume ratio of the acetonitrile and dimethyl sulfoxide is 4:6, the copper iodide semiconductor material or thin film produced may have a hole mobility approximately three times higher than that of the prior art produced using a single solvent.

[0052] In another embodiment, the mixed solvent may include acetonitrile and γ-butyrolactone. The γ-butyrolactone may be added in an amount of 40% or less relative to the total mixed solvent. If this amount is exceeded, there may be a problem in that the copper iodide powder is not uniformly dissolved in the mixed solution. Therefore, preferably, the volume ratio of acetonitrile and γ-butyrolactone in the mixed solvent may be greater than 8:2 and less than or equal to 6:4.

[0053] In another embodiment, the mixed solvent may include acetonitrile and dimethylformamide. The dimethylformamide may be added in an amount of 40% or less relative to the total mixed solvent. If this amount is exceeded, there may be a problem in that the copper iodide powder is not uniformly dissolved in the mixed solution. Therefore, preferably, the volume ratio of acetonitrile and dimethylformamide in the mixed solvent may be greater than 8:2 and less than or equal to 6:4.

[0054] The above mixed solution may be prepared and / or stored in an inert atmosphere. The inert atmosphere may be created using at least one of N2, Ar, and He, but the type of gas is not specifically limited, and any substance capable of providing an inert atmosphere is acceptable. When stored in an inert atmosphere, the mixed solution can be stored in a uniformly mixed state without precipitates. Therefore, preferably, the mixed solution may be stored in an inert atmosphere after preparation.

[0056] The mixed solution for manufacturing a copper iodide semiconductor material according to the present invention provides a copper iodide semiconductor material having high crystallinity, a uniform thin film, and high dynamic mobility compared to conventional technology using a single solvent system by using a mixed solvent system.

[0058] Hereinafter, the present invention will be described in more detail through an embodiment of the present invention and the analysis results of said embodiment.

[0060] Example 1

[0061] A mixed solution was prepared by dissolving copper iodide powder in a mixed solvent in which acetonitrile and γ-butyrolactone were mixed in various volume ratios (10:0, 8:2, 6:4, 4:6, 2:8, 0:10).

[0063] Example 2

[0064] A mixed solution was prepared by dissolving copper iodide powder in a mixed solvent in which acetonitrile and dimethylformamide were mixed in various volume ratios (10:0, 8:2, 6:4, 4:6, 2:8, 0:10).

[0066] Example 3

[0067] A mixed solution was prepared by dissolving copper iodide powder in a mixed solvent in which acetonitrile and dimethyl sulfoxide were mixed in various volume ratios (10:0, 8:2, 6:4, 4:6, 2:8, 0:10).

[0069] Solubility evaluation

[0070] Figure 3 is the result of evaluating the solubility of copper iodide powder in a mixed solution (ACN:γ-butyrolactone) according to Example 1 of the present invention.

[0071] Referring to Fig. 3, it was confirmed that when a mixed solvent containing acetonitrile (ACN) and γ-butyrolactone was used, the copper iodide powder was not completely dissolved when the volume ratio of γ-butyrolactone in the mixed solvent exceeded 40% relative to the mixed solvent.

[0073] Figure 4 is the result of evaluating the solubility of copper iodide powder in a mixed solution (ACN:DMF) according to Example 2 of the present invention.

[0074] Referring to Figure 4, it was confirmed that when a mixed solvent containing acetonitrile (ACN) and dimethylformamide (DMF) was used, the copper iodide powder was not completely dissolved when the volume ratio of dimethylformamide in the mixed solvent exceeded 40% relative to the mixed solvent.

[0076] Referring to FIG. 5, the solubility of copper iodide powder in a mixed solution (ACN:DMSO) according to Example 3 of the present invention was evaluated.

[0077] Referring to Figure 5, it was confirmed that copper iodide powder was completely dissolved in all volume ratios when a mixed solvent containing acetonitrile (ACN) and dimethylsulfoxide (DMSO) was used.

[0079] Figure 6 is the result of evaluating whether copper iodide powder precipitates in a mixed solution (ACN:DMSO) according to Example 3 of the present invention.

[0080] Referring to Figure 6, when a mixed solution containing a mixed solvent including acetonitrile (ACN) and dimethyl sulfoxide is exposed to air for 10 minutes, it can be observed that the mixed solution changes to a dark brown color and a black precipitate settles. This confirms that the mixed solution is stored and / or prepared in an inert atmosphere, and that care must be taken during spin coating.

[0082] As confirmed in the above experiment, it was confirmed that when using a mixed solvent containing acetonitrile (ACN) and dimethyl sulfoxide (DMSO), the solubility of copper iodide powder and the formation of a uniform solution phase were achieved at all volume ratios. Therefore, a copper iodide semiconductor thin film was prepared below using a mixed solvent containing acetonitrile (ACN) and dimethyl sulfoxide (DMSO). First, a mixed solution was prepared by dissolving copper iodide powder in a mixed solvent containing acetonitrile (ACN) and dimethyl sulfoxide (DMSO), and a copper iodide thin film was formed by spin-coating the mixed solution onto a substrate. Then, the copper iodide thin film was heat-treated at 80°C for 10 minutes to prepare a copper iodide semiconductor material thin film according to one embodiment of the present invention.

[0084] Crystal structure analysis

[0085] Figure 7 is a diagram comparing the X-ray diffraction patterns of copper iodide thin films prepared using a single solvent (ACN) and a mixed solvent (ACN:DMSO=4:6) according to one embodiment of the present invention.

[0086] Referring to Fig. 7, it can be seen that the CuI (111) diffraction signal of the copper iodide thin film using a mixed solvent of acetonitrile and dimethylsulfoxide (ACN:DMSO) is higher than that of the copper iodide thin film using a single solvent of acetonitrile (ACN).

[0087] Through this, it can be seen that a thin film with higher crystallinity is formed when a mixed solvent is used.

[0089] FIG. 8 is a diagram comparing the X-ray diffraction patterns of a copper iodide thin film prepared using a mixed solvent according to one embodiment of the present invention before and after heat treatment.

[0090] Referring to FIG. 8, when a single solvent was used (CuI reference), diffraction signals of the crystal planes (200), (220), and (222) were observed. On the other hand, when a mixed solvent was used, before annealing, diffraction signals of the crystal planes of CuI (111), CuI (220), and CuI (311) were observed. Meanwhile, after annealing, a single strong diffraction signal of the CuI (111) crystal plane could be observed.

[0091] Through this, it can be seen that higher quality CuI thin films can be formed as the intermediate phase thin film grows stably through heat treatment.

[0093] Surface shape analysis

[0094] Figure 9 is a diagram comparing AFM surface morphology images of copper iodide thin films prepared using a single solvent (ACN) and a mixed solvent (ACN:DMSO=4:6) according to one embodiment of the present invention.

[0095] Referring to Fig. 9, it can be seen that the copper iodide thin film using acetonitrile (ACN) as a single solvent has locally broken film. On the other hand, it can be seen that the copper iodide thin film using a mixed solvent of acetonitrile and dimethylsulfoxide (ACN:DMSO) has a continuous film shape.

[0097] FIG. 10 shows secondary electron microscope images of a copper iodide thin film prepared using a mixed solvent (ACN:DMSO = 4:6) according to one embodiment of the present invention, before and after heat treatment, respectively. FIG. 10a and FIG. 10b show surface morphology images of the copper iodide thin film using the mixed solvent immediately after spin coating at magnifications of 5,000x and 50,000x, respectively. FIG. 10c and FIG. 10d show surface morphology images of the copper iodide thin film using the mixed solvent after heat treatment at magnifications of 5,000x and 50,000x, respectively. FIG. 10e and FIG. 10f show surface morphology images at magnifications of 5,000x and 50,000x, respectively, confirmed by heat treating the sample of FIG. 10a immediately after measurement.

[0098] Referring to Fig. 10, the surface morphology of the CuI thin films can be observed through a secondary electron microscope. Specifically, referring to Fig. 10a and Fig. 9b, before heat treatment, white copper iodide crystal nuclei are arranged in a disordered manner on a dark gray intermediate phase thin film. Referring to Fig. 10c and Fig. 10d, it can be seen that after heat treatment, CuI crystals form a continuous thin film with high density.

[0099] Meanwhile, referring to Figures 10e and 10f, it can be confirmed that the heat treatment process immediately after spin coating is a key factor in the formation of a continuous and highly crystalline thin film. Figures 10e and 10f are images of the surface morphology of the same sample observed again after heat treatment in an inert atmosphere immediately after acquiring secondary electron microscope images of the CuI thin film corresponding to Figures 10a and 10b. As with Figures 10c and 10d, it can be confirmed that although crystallization proceeded, a discontinuous thin film was grown due to exposure to atmospheric and vacuum environments.

[0101] FIG. 11 is an AFM surface morphology image of a copper iodide thin film prepared using a mixed solvent (ACN:DMSO = 4:6) according to one embodiment of the present invention when sufficiently exposed to air without heat treatment.

[0102] Referring to Fig. 11, it can be seen that the copper iodide thin film prepared using a mixed solvent (ACN:DMSO = 4:6) exposed to air without heat treatment has a discontinuous and very rough surface.

[0104] FIG. 12 is an AFM surface morphology image of a copper iodide thin film prepared using a mixed solvent (ACN:DMSO = 4:6) according to one embodiment of the present invention after heat treatment.

[0105] Referring to Fig. 12, it can be seen that a continuous and smooth surface shape is obtained when heat treatment in an inert atmosphere is performed immediately after spin coating. When compared to the results in Fig. 11, it can be seen that although exposure to air induces the decomposition of the intermediate phase thin film and the growth of the copper iodide thin film, heat treatment of the copper iodide thin film in an inert atmosphere immediately after spin coating is key to obtaining a high-quality CuI thin film.

[0107] Hall Effect Measurement and Hole Mobility Analysis

[0108] FIG. 13 is a figure showing the results of measuring the Hall effect of a copper iodide semiconductor thin film prepared using a mixed solvent (ACN:DMF and ACN:DMSO) mixed in various volume ratios according to one embodiment of the present invention.

[0109] Referring to Fig. 13, it can be confirmed that the conductivity and hole mobility of the copper iodide semiconductor thin film at ACN:DMF = 8:2 and 6:4 do not differ significantly from those of the copper iodide semiconductor thin film using pure ACN as the solvent. On the other hand, at ACN:DMSO = 8:2 and 6:4, a significant difference was observed compared to the results of the copper iodide semiconductor thin film using pure ACN as the solvent.

[0111] To determine the volume ratio of the optimized mixed solvent (ACN:DMSO), the hole mobility of copper iodide semiconductor thin films prepared according to the volume ratio was analyzed, and the results are shown in Figure 14.

[0113] FIG. 14 is a figure showing the results of measuring the hole mobility of a copper iodide semiconductor thin film prepared using a mixed solvent (ACN:DMSO) mixed in various volume ratios (10:0, 8:2, 6:4, 4:6, 2:8, 0:10) according to one embodiment of the present invention.

[0114] Referring to Fig. 14, it can be seen that the trends in electrical conductivity and hole mobility of each copper iodide semiconductor thin film are identical. This implies that each thin film has a similar hole concentration. Among them, the hole mobility of the copper iodide semiconductor thin film using an ACN:DMSO=4:6 mixed solvent is 15.6 cm⁻¹ 2 5.6 cm of copper iodide semiconductor thin film using the existing technology ACN single solvent (ACN:DMSO=10:0) with / Vs 2 It showed mobility about three times higher than / Vs.

[0115] As such, the fact that there is a threefold improvement in hole mobility without a change in hole concentration means that improvements in crystallinity and electrical properties can be achieved without an increase or decrease in crystal defects simply by using a mixed solvent system.

[0117] Although the present invention has been described in detail using preferred embodiments, the scope of the invention is not limited to specific embodiments and should be interpreted by the appended claims. Furthermore, those skilled in the art will understand that many modifications and variations are possible without departing from the scope of the invention.

Claims

Claim 1 A method for manufacturing a copper iodide semiconductor material, comprising a thin film formation step of forming a thin film by spin-coating a mixed solution in which copper iodide powder is dissolved in a mixed solvent onto a substrate, and a heat treatment step of annealing the thin film, wherein the mixed solvent comprises acetonitrile and dimethyl sulfoxide, and the volume ratio of acetonitrile and dimethyl sulfoxide is greater than 2:8 and less than or equal to 4:

6. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 delete Claim 8 A method for manufacturing a copper iodide semiconductor material, wherein, in claim 1, the thin film formation step is performed in an inert atmosphere. Claim 9 A method for manufacturing a copper iodide semiconductor material, wherein, in claim 8, the inert atmosphere is formed using at least one of N2, Ar, and He. Claim 10 A method for manufacturing a copper iodide semiconductor material according to claim 1, wherein the heat treatment step is performed at 70°C to 90°C. Claim 11 A mixed solution for manufacturing a copper iodide semiconductor material, wherein copper iodide powder is dissolved in a mixed solvent, the mixed solvent comprises acetonitrile and dimethyl sulfoxide, and the volume ratio of acetonitrile and dimethyl sulfoxide is greater than 2:8 and less than or equal to 4:

6. Claim 12 delete Claim 13 delete

Citation Information

Patent Citations

  • Preparation method of perovskite nanostructures and the perovskite nanostructures thereby

    KR1020170052761A

  • Perovskite solar cell comprising surface-treated electron transport layer and method of manufacturing the same

    KR1020200040954A

  • Optoelectronic device and method for fabricating active layer for optoelectronic device

    KR1020240163433A

  • Perovskite compositions comprising mixed solvent systems

    CN112166160A

  • Thin film transistor having a CuI channel layer and method of manufacturing the same

    KR1020200084653A